Implementasi Konsumsi Islami Pada Pengajar Pondok Pesantren (Studi Kasus Pada Pengajar Pondok Pesantren Al Aqobah Kecamatan Diwek Kabupaten Jombang) - Baidhowi, Bagus; Zaki, Irham (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to determine the application of Islamic consumption by Al Aqobah Boarding School teacher in Diwek Subdistrict, Jombang District.This study used a qualitative approach with descriptive case study method. The population characteristics of this study are the teachers of Al Aqobah Boarding School in Diwek Subdistrict, Jombang District. The teachers of Al Aqobah Boarding School who know and understand the consumption according to Islam are people who implement Islamic consumption in his life, the teacher/ustadz and ustadzah who has been teaching at Al Aqobah boarding school at least 2 years. The number of samples in this study was six informants. The sampling technique used was purposive sampling.Based on the results of this study showed that Al Aqobah boarding school teacher in Diwek Subdistrict, Jombang District, has implemented the Islamic consumption legally (halal); they are not extravagant not only in spending wealth but also in living luxury and showing assets. They can also make the balance system between worldly and hereafter consumption.Moreover, the suggestion for all of people in Al Aqobah boarding school and also the teachers are expected to continue teaching the consumption which is true to Islam, apply in everyday life, and provide appropriate examples to the students. For further research, it is expected to examine the same topic with more in depth details about the implementation of Islamic consumption on other aspects that are more specific.